Forms and Constraints of Services for Elderly Hajj Pilgrims at the Ministry of Religious Affairs of Soppeng Regency - Ali, Sitti Asiqah Usman; Tenriawaru, Andi Nurlaily; Aderus, Andi Fadhil Andi; Rasna, Rasna (Fakultas Syariah Institut Agama Islam Negeri Palu, 2025)
The purpose of this study was to examine the forms and constraints of services to elderly pilgrims at the Ministry of Religion of Soppeng Regency. This research is qualitative research, the type of research is field research. The data collection methods used are observation, interview, and documentation. The results showed that: 1) There are several forms of services for elderly pilgrims at the Ministry of Religion of Soppeng Regency, including administrative services, namely serving elderly pilgrims in preparing all documents before departure by door to door, then manasik services, namely providing initial provision for elderly pilgrims to get education about what will be done before leaving until arriving back in the country, then health services, elderly pilgrims receive special attention considering their limitations and have a higher rate of disease, all services carried out by the Ministry of Religion of Soppeng Regency are carried out wholeheartedly like their own parents. 2) Obstacles in the implementation of services to elderly pilgrims at the Ministry of Religion of Soppeng Regency, namely health and physical condition constraints, elderly pilgrims have a physical condition that is decreasing due to age factors and have several health problems both congenital and easily affected by illness besides that elderly pilgrims have obstacles in communication limitations and stuttering technology, obstacles like this are often encountered for an elderly person, but with a sophisticated era the Ministry of Religion has experienced few obstacles when serving elderly pilgrims because they must be guided properly and taught repeatedly until they understand.